EEG dynamics on hyperbolic manifolds. (14th September 2018) - Tozzi, Arturo; Peters, James F.; Jaušovec, Norbert
Highlights: EEG dynamics take place in a three-dimensional Euclidean environment. They can tranferred to a hyperbolic, concave maniford with negative curvature. This transfer allows a better assessment and quantification of EEG traces' undetectable features. Abstract: Biological activities, including cellular metabolic pathways, protein folding and brain function, can be described in terms of curved trajectories in hyperbolic spaces which are constrained by energetic requirements. Here, starting from theorems recently-developed by a deceased Field Medal young mathematician, we show how it is feasible to find and quantify the shortest, energy-sparing functional trajectories taking place in nervous systems' concave phase spaces extracted from real EEG traces. This allows neuroscientists to focus their studies on the few, most prominent functional EEG's paths and loops able to explain, elucidate and experimentally assess the rather elusive mental activity.